2016
DOI: 10.1186/s12936-016-1412-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors for Plasmodium infection and anaemia in Kinshasa, Democratic Republic of Congo

Abstract: BackgroundThere is little data on the risk factors for malaria infection in large cities in central Africa and in all age groups. There may be different associations with the risk factors for areas with different malaria transmission intensities such as the effect of fever or age. This study aimed at identifying risk factors associated with Plasmodium infection and anaemia among children 6–59 months and individuals aged older than 5 years in Kinshasa, a large city with heterogeneity in malaria prevalence.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 29 publications
4
31
2
Order By: Relevance
“…The age specific pattern observed has been reported by other researchers in different contexts including DRC, [11, 2325]. Interestingly, in this study, the same pattern was observed even in households possessing sufficient numbers of LLIN to cover all residents, suggesting a behavioural gap in LLIN use among older children and adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…The age specific pattern observed has been reported by other researchers in different contexts including DRC, [11, 2325]. Interestingly, in this study, the same pattern was observed even in households possessing sufficient numbers of LLIN to cover all residents, suggesting a behavioural gap in LLIN use among older children and adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…Behavioural factors may have also contributed to rapid shifts in the age distribution of malaria. A reduced proportion of cases among children under 5 years of age may have been due to an increased use of LLINs among this age group relative to older age groups [22,41,42]. In adults, behavioural factors including travel, leisure and social activities, and occupational activities such as agriculture or night-time work may have increased the risk of exposure outside the household as compared to children.…”
Section: Discussionmentioning
confidence: 99%
“…This allows us to make inferences regarding the country as a whole. Other recent malaria risk factor studies have fewer individuals or are conducted in a smaller geographic area 11,12 . Second, we determined malaria infection using high-throughput real-time PCR, the most sensitive method for diagnosing infection 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies performed in the DRC have identified important risk factors for infection 4,9,10 . These studies showed that increasing age, wealth, and individual bed-net use are protective, as are increasing community level bed-net use, lower average temperature and higher altitude [9][10][11][12] . However, these studies included only children under the age of five 9,10 , or were small and geographically limited 11,12 .…”
Section: Introductionmentioning
confidence: 99%